ChemInform Abstract: Computational Methods for the Design of Potent Aromatase Inhibitors. Issue 35 (8th August 2013) - Favia, Angelo Danilo; Nicolotti, Orazio; Stefanachi, Angela; Leonetti, Francesco; Carotti, Angelo
Abstract Review: 103 refs.